Beta-Carotene, Glycemic Control And Dyslipidemia In Type 2 Diabetes Mellitus - Mohammed, Hayder Ali; Al-Shamma, Ghassan A.; Hashim, Hashim M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background : Diabetes mellitus is a stressful condition in which the increased production of free radicals impairs the generation of naturally occurring antioxidants like vitamins and carotenoids . Aim :The present study deals with the changes in serum ß-carotene in type 2 diabetes mellitus, as modulated by glycemic control and oxidative stress . Subjects & methods : Multiple biochemical parameters were obtained from plasma of 57 patients with type 2 diabetes mellitus ( 25 males and 32 females ) , on oral hypoglycemic with a disease duration of 1- 15 years and 37 healthy normal subject s of matching age and sex to serve as controls. The biochemical parameters measured in the present study included the glycated Hb (HbA1c ), serum lipids ( total cholesterol TC, triglycerides TG , high and low density lipoprotein cholesterols , HDL-C & LDL-C ) , lipid peroxides and serum ß-carotene. results revealed a marked reduction of ß- carotene in the diabetics in a pattern proportional to that of the glycemic control ,dyslipidemia and oxidative stress . Possible causes , mechanisms and suggestions underlining these changes are discussed.